IL-28B genetic variation, gender, age, jaundice, hepatitis C virus genotype, and hepatitis B virus and HIV co-infection in spontaneous clearance of hepatitis C virus - Fedorchenko, Sergii V.; Klimenko, Anna; Martynovich, Tetyana; Liashok, Olga; Yanchenko, Vitaliy (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Spontaneous viral clearance observed in some patients is one of the variants of the hepatitis C virus (HCV) infection natural history. We aimed to look at the complexity of factors affecting the spontaneous clearance of HCV (SC HCV). Materials and Methods: A total of 357 anti-HCV positive patients (309 with chronic hepatitis C and 48 patients with SC HCV) were included into the study. We studied the effects of the interleukin-28B (IL-28B) gene polymorphism, gender, age, the routes of virus transmission, past hepatitis C with jaundice, HCV genotype, and hepatitis B virus (HBV) and HIV co-infection on the outcome of HCV infection. Results: Based on the study results, the SC HCV was found in 48 individuals (13.4%). The most significant positive factors affecting the SC HCV included IL-28B single nucleotide polymorphism (SNP) rs12979860 (CC) and SNP rs8099917 (TT) (OR 4.03, p Conclusion: Positive predictors of the SC HCV include favorable IL-28B genotype, female gender, young age, a history of jaundice, markers of a past HBV infection, the absence of HIV infection, but not the viral genotype. Cite this article as: Fedorchenko SV, Klimenko A, Martynovich T, Liashok O, Yanchenko V. IL-28B genetic variation, gender, age, jaundice, hepatitis C virus genotype, and hepatitis B virus and HIV co-infection in spontaneous clearance of hepatitis C virus. Turk J Gastroenterol 2019; 30(5): 436-44.